Current outcome of HLA identical sibling versus unrelated donor transplants in severe aplastic anemia: an EBMT analysis - Andrea Bacigalupo; Gerard Socié; Rose Marie Hamladji; Mahmoud Aljurf; Alexei Maschan; Slawomira Kyrcz-Krzemien; Alicja Cybicka; Henrik Sengelov; Ali Unal; Dietrich Beelen; Anna Locasciulli; Carlo Dufour; et al. (Haematologica, 2015)
We have analyzed 1448 patients with acquired aplastic anemia grafted between 2005 and 2009, and compared outcome of identical sibling (n=940) versus unrelated donor (n=508) transplants. When compared to the latter, sibling transplants were less likely to be performed beyond 180 days from diagnosis (39% vs. 85%), to have a cytomegalovirus negative donor/recipient status (15% vs. 23%), to receive antithymocyte globulin in the conditioning (52% vs. 61%), and more frequently received marrow as a stem cell source (60% vs. 52%). Unrelated donor grafts had significantly more acute grade II–IV (25% vs. 13%) and significantly more chronic graft-versus-host disease (26% vs. 14%). In multivariate analysis, the risk of death of unrelated donor grafts was higher, but not significantly higher, compared to a sibling donor (P=0.16). The strongest negative predictor of survival was the use of peripheral blood as a stem cell source (P